Early Weaning Stress Induces Intestinal Microbiota Disturbance, Mucosal Barrier Dysfunction and Inflammation Response Activation in Pigeon Squabs - Xu, Qianqian; Jian, Huafeng; Zhao, Wenyan; Li, Jiankui; Zou, Xiaoting; Dong, Xinyang (Frontiers in Microbiology, 2022)
Early weaning stress has been reported to impair intestinal health in mammals. Like mammals, weaning of the pigeon squab, an altricial bird, is associated with social, environmental and dietary stress. However, understanding of weaning stress on intestinal functions is very limited in altricial birds, especially in squabs. This study was aimed to evaluate the effects of early weaning stress on intestinal microbiota diversity, architecture, permeability, the first line defense mechanisms, mucosal barrier functions, and immune cell responses. A total of 192 newly hatched squabs were randomly allocated into two groups, one weaned on day 7 and the other remained with the parent pigeons. Mucosal tissue and digesta in ileum, as well as blood samples, were collected from squabs (n = 8) on days 1, 4, 7, 10, and 14 postweaning. Our results showed that weaning stress induced immediate and long-term deleterious effects on both growth performance and intestinal barrier functions of squabs. Early weaning significantly increased ileal bacterial diversity and alters the relative abundance of several bacteria taxa. Weaning stress can also cause morphological and functional changes in ileum, including an atrophy in villi, an increase in permeability, and a variation in the mRNA expression of genes encoding mucins, immunoglobulins, tight junction proteins, toll-like receptors, and cytokines, as well as the concentration of secretory IgA. We concluded that the impaired intestinal barrier functions accompanied with early weaning stress seems to be the main reason for the poor growth rate after weaning in squabs. In addition, the disturbance of intestinal microbiota of early weaning stress in squabs coincided with dysfunction of intestinal mucosal barrier and activation of inflammation cell responses that were possibly mediated via the activation of toll-like receptors.